Can patients with low‐risk prostate cancer really benefit from radical treatment?: A systematic review and network meta‐analysis. (28th July 2021) - Zhen, Liang; Zhien, Zhou; Shengmin, Yang; Hanzhong, Li; Xingcheng, Wu; Yi, Zhou; Yi, Qiao; Lin, Ma; Yuliang, Chen; Tianrui, Feng; Weigang, Yan
Abstract: Radical prostatectomy, radiotherapy and active surveillance are three widely used treatment options for patients with low‐risk prostate cancer, but the relative effects are controversial. We searched PubMed, Embase and Web of Science until June 2020, focusing on the studies comparing the effect of radical prostatectomy, radiotherapy and active surveillance in patients with low‐risk prostate cancer. Through the random‐effects model, dichotomous data were extracted and summarised by odds ratio with a 95% confidence interval. Twenty‐two studies containing 185, 363 participants were pooled for the comprehensive comparison. The Bayesian mixed network estimate demonstrated the cancer‐specific mortality of radical prostatectomy was significantly lower than active surveillance (OR, 0.46; 95% CI 0.34–0.64) and external beam radiation therapy (OR, 0.66; 95% CI 0.46–0.96), but not brachytherapy (OR, 0.63; 95% CI 0.41–1.03). The brachytherapy demonstrated the best treatment ranking probability results in terms of all‐cause mortality, while no significant difference was observed when compared with other three treatment modalities. Brachytherapy and radical prostatectomy were associated with a similar risk of cancer‐specific mortality, and both of them were significantly superior to active surveillance and external beam radiation therapy; nevertheless, there was no significant difference among the aforementioned treatment methods in all‐cause mortality.